Basement Kind Effects on Air Temperature of a Solar Chimney in Baghdad - Iraq Weather - Chaichan, Miqdam Tariq (Al-Khwarizmi Engineering Journal, 2019)
A solar updraft tower power plant (solar tower) is a solar thermal power plant that utilizes a combination of solar air collector and central updraft tube to generate an induced convective flow which drives pressure staged turbines to generate electricity. This paper presents practical results of a prototype of a solar chimney with thermal mass, where the glass surface is replaced by transparence plastic cover. The study focused on chimney’s basements kind effect on collected air temperatures. Three basements were used: concrete, black concrete and black pebbles basements. The study was conducted in Baghdad from August to November 2009. The results show that the best chimney efficiency attained was 49.7% for pebbles base. The highest collected air temperature reached was 49ºC when using the black pebbles basement also.also, the maximum basement temperature measured was 59ºC for black pebbles. High increaments in collected air temperatures were achieved in comparison with the ambient air temperatures for the three basement kinds. The highest temperature difference reached was 22ºC with the pebble ground.